PENGARUH HARGA, KUALITAS PRODUK DAN BRAND AMBASSADOR TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING DIKOTA PEKANBARU - Zafira Hasna; Jushermi Jushermi; Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to determine the effect of price, product quality and brand ambassador onpurchasing decisions and customer satisfaction of scarlett whitening products in Pekanbarucity. The population in this study were consumers who bought and used scarlett whiteningproducts in Pekanbaru city, the number of which is not known for sure. Sampling usednonprobability sampling with purposive sampling technique and 120 people were selected tobe samples. The data analysis method used structural equation model (SEM) with the helpof SmartPLS software version 3.0. The results of the study showed that: 1) Price has apositive and significant effect on purchasing decisions; 2) Product quality has a positive andsignificant effect on purchasing decisions; 3) Brand ambassador has a positive andsignificant effect on purchasing decisions; 4) Purchasing decisions have a positive andsignificant effect on customer satisfaction; 5) Price has a positive and significant effect oncustomer satisfaction through purchasing decisions; 6) Product quality has a positive andsignificant effect on customer satisfaction through purchasing decisions; 7) Brandambassador has a positive and significant effect on customer satisfaction throughpurchasing decisions.Keywords: Price, Product Quality, Brand Ambassador, Purchasing Decision and CustomerSatisfaction